Benthic foraminiferal carbon cycling in coastal zone sediments: The influence of the assemblage structure and jellyfish detritus. (31st October 2021) - Klootwijk, Anouk T.; Sweetman, Andrew K.; Hess, Silvia; Alve, Elisabeth; Dunlop, Kathrine M.; Renaud, Paul E.
Abstract: Jellyfish carrion is an important carbon source to the benthic ecosystem that is expected to increase in some regions in the future, but its potential impact on sediment biochemical processes is not fully understood. Benthic foraminifera play important carbon processing roles in marine ecosystems but little is known about how they process carbon within fjords, or how jellyfish detritus on the sediment may affect this role. This study is the first to use 13 C-labelled algae to quantify how jellyfish detritus may alter benthic foraminiferal microalgal-carbon uptake (C-uptake) from the inner to outer fjord. To assess potential mechanisms for variations in C-uptake, foraminiferal biomass, density, and assemblage composition, in addition to the sediment O2 dynamics and environmental parameters (e.g. sediment total organic carbon [TOC] content) were investigated. Benthic foraminiferal C-cycling strongly varied within the fjord with 20-times higher C-uptake rates at the inner-fjord location compared to the locations further outwards. This difference was likely caused by the higher foraminiferal biomass and relative abundances of Bulimina marginata and Nonionella turgida at the inner location. Strong differences in foraminiferal assemblage structure amongst the locations were not explained by major differences in the investigated environmental parameters. Changes in sediment O2 dynamics suggested that jellyfish detritus obstructed O2 diffusion into the sediment. A potential effect of these changes on the C-uptake was only observed at the inner location, indicating the effect of jellyfish detritus on foraminiferal C-uptake rates was little and dependent on the benthic foraminiferal assemblage composition (e.g. the presence of B. marginata ). This suggests that the areas in coastal zones where the highest amounts of organic carbon are being processed may also be the most sensitive to changes in the sediment O2 dynamics, which would make them vulnerable to changes in riverine input and anthropogenic organic carbon enrichment. Graphical abstract: Image 1 Highlights: Foraminifera carbon-uptake 20 fold higher at the inner-fjord than further outwards. Biomass, density and assemblage composition drove strong differences in C-uptake. Short-term exposure to jellyfish had little impact on foraminiferal C-uptake. Sediment O2 dynamics suggested potential smothering effect from jellyfish detritus.